Answer:
No
Step-by-step explanation:
Answer:
7**6
Step-by-step explanation:
The expression 7^6 ; can be interpreted as 7 raised to the power of 6 ; which is (7 * 7 * 7 * 7 * 7 * 7). To execute this expression using a computer or basic mathematical operation on a computer we use the power symbol which the computer understand this the double multiplication symbol (**)
Hence, 7^6 = (7**6)
Answer:
The roots are;
x = (2 + i)/5 or (2-i)/5
where the term i is the complex number representing the square root of -1
Step-by-step explanation:
Here, we want to use the completing the square method to solve the quadratic equation;
f(x) = -5x^2 + 4x -1
Set the function to zero
0 = -5x^2 + 4x - 1
So;
-5x^2 + 4x = 1
divide through by the coefficient of x which is -5
x^2 - 4/5x = -1/5
We now take half of the coefficient of x and square it
= -2/5^2 = 4/25
add it to both sides
x^2 - 4x/5 + 4/25= -1/5 + 4/25
(x- 2/5)^2 = -1/5 + 4/25
(x - 2/5)^2 = -1/25
Take the square root of both sides
x - 2/5 = √( -1/25
x - 2/5 = +i/5 or -i/5
x = 2/5 + i/5 or 2/5 - i/5
ratio of vertical change between 2 points
D, 8.5
a squared + b squared = c squared for the sides and hypotenuse of the triangle.
6^2 + 6^2 = c^2
36 + 36 = c^2
72 = c^2
c = square root of 72, 8.49